CASH WAQF INVESTMENT MANAGEMENT IN INDONESIA: STUDY OF LITERATURE - Kamal, Jaidil; Soemitra, Andri; M. Nawawi, Zuhrinal (CV. Radja Publika, 2022)
Waqf, especially cash waqf, is essentially an investment where the owner wants to endow his wealth so that the results can be obtained at the end (yaumulqiyamah). This can be done while maintaining the principal, such as waqf of trees, fruitful gardens, rental proceeds on leased goods, or in the form of dividends or income such as cash waqf. The purpose of this research is to find out the management of cash waqf investment management in order to be more productive. This research is a type of descriptive qualitative and content analysis literature study. The results of this study indicate that investment management carried out in cash waqf investments is allocated to two aspects, namely social and productive. The social aspect includes mosque donations, Qur'anic waqf, scholarships for orphans, and the poor. in the productive aspect, including investment in fattening goats and other businesses managed by third parties in collaboration with waqf managers. The problem faced by managers in terms of investment management is the lack of supervision and focus on the waqf property itself. This is because there are many programs other than the waqf program that must be prioritized. The management of waqf investment has indeed been managed productively, but for the utilization of the results it cannot be used productively so that the mauquf 'alaih cannot fully feel the benefits.